Heart rate lowering agents in acute coronary syndrome - Banjara, Prabhudev R.; Ramaiah, Balakeshwa; P. Gudur, Shreya (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Heart rate is a key indicator of cardiovascular mortality, with ACS having the highest mortality risk when heart rate is elevated. With a target heart rate of <70 bpm, it is crucial to evaluate the effects of medications that lowers heart rate. Methods: In this prospective observational study, 45 patients with ACS were studied, and it was determined whether or not the patients' heart rates at discharge from the hospital were within goal range. Additionally, we looked at demographics, drug-related issues, vitals and then statistical tests were performed. Results: The demographic of 45 patients showed mean adult age was 47 years and most observed ACS was STEMI (53.3%). Patients prescribed with HRLA showed lower mean HR, SBP and DBP at discharge. Evaluated Optimal HR ≤70 bpm with HRLA therapy at discharge of the inpatients was achieved in 26.6% (63.5±5.5 bpm). Conclusions: The current study showed HRLA therapy effectively reduced the heart rate at hospital discharge, but despite being on HRLA only 1/4th of patients achieved the optimal heart rate.